Pathways to Mitigate Challenges of Learner Academic Performance in a Grade 10 Economics Class in South Africa - Habasisa Vincent Molise (Research in Social Sciences and Technology- OpenED Network, 2021)
This paper aims to explore the pathways to mitigate challenges of learner academic (LAP) performance in a Grade 10 economics class in South Africa. The challenge of poor LAP has ushered a myriad of predicaments in schools globally. These predicaments include lack of teacher inclusion in decision making, inability to work cooperatively together, and lack of professional development opportunities geared towards LAP. The study was qualitative, with 15 participants chosen through purposeful sampling from one rural school in the Thabo-Mofutsanyane education district. This paper is couched in critical emancipatory research with emphasis on the emancipation of the teachers regarding pathways they can self-develop to mitigate the challenges of LAP. The focus group discussions were used to gather information regarding pathways to mitigate the challenges of LAP in schools. The study revealed that teachers possess a very equivocal and varying experience regarding the pathways to use to mitigate the challenges of LAP. The findings suggest that for successful implementation of pathways to mitigate the challenges of LAP, schools need to invest in training teachers for team-teaching and avail the necessary resources (both human and physical) to ensure effective quality teaching and learning exist in the school. The article recommends that schools should develop policy frameworks, together with relevant stakeholders, to guide novice teachers on the strategies they can use to mitigate the challenges of LAP in their classes.